2019
DOI: 10.1111/1348-0421.12686
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of Helicobacter pylori antibiotic resistance in the Taif region, Saudi Arabia

Abstract: Success in eradication of Helicobacter pylori is declining globally because H. pylori has developed resistance against most of the antibiotics proposed for eradication regimens, mainly through point mutations. The present study included 200 patients with dyspepsia attending Taif Hospital. Gastric biopsies were obtained during gastroscopy and subjected to rapid urease testing. Molecular methods were used to confirm diagnoses of H. pylori infection and to identify resistance gene variants of four antibiotics; na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
7
1
Order By: Relevance
“…Compared to the data from Eastern Mediterranean, the resistance rate to clarithromycin was two times higher in our study (WPR 21%, 95% CI 16‐26) than was observed in Egypt (WPR 56%, 95% CI, 47‐64) and Pakistan (WPR 40%, 95% CI 32‐49) yet at the same level as that reported in Saudi Arabia (WPR 23%, 95% CI 15‐34) 13 ; however, the latest data from Saudi Arabia suggest there is an increasing trend toward resistance (39.9%) 83 . The highest resistance rate for metronidazole identified in our study (WPR 62%, 95% CI 57‐67) is in the line with data from Pakistan and Egypt (WPR 62%, 95% CI 51‐74 and WPR 63%, 95% CI 51‐73), and although slightly lower in Saudi Arabia (WPR 49%, 95% CI 37‐60), 13 the resistance is still high.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Compared to the data from Eastern Mediterranean, the resistance rate to clarithromycin was two times higher in our study (WPR 21%, 95% CI 16‐26) than was observed in Egypt (WPR 56%, 95% CI, 47‐64) and Pakistan (WPR 40%, 95% CI 32‐49) yet at the same level as that reported in Saudi Arabia (WPR 23%, 95% CI 15‐34) 13 ; however, the latest data from Saudi Arabia suggest there is an increasing trend toward resistance (39.9%) 83 . The highest resistance rate for metronidazole identified in our study (WPR 62%, 95% CI 57‐67) is in the line with data from Pakistan and Egypt (WPR 62%, 95% CI 51‐74 and WPR 63%, 95% CI 51‐73), and although slightly lower in Saudi Arabia (WPR 49%, 95% CI 37‐60), 13 the resistance is still high.…”
Section: Discussioncontrasting
confidence: 55%
“…The limitation of our study is the inclusion of the overall resistance rates in the meta‐analyses which does not allows a distinction between primary and secondary resistance rates. As the data from the same region show, a significant difference between primary and secondary resistance can be expected with clarithromycin but not with the fluoroquinolones, tetracycline, and metronidazole 83 …”
Section: Discussionmentioning
confidence: 94%
“…34 The overall resistance to CLR in Saudi Arabia was reported to range between 23-40%. 35,36 Several studies have linked the 23s rRNA gene mutations of H. pylori, including A2142G, A2143G, or T2182C, among others, to CLR resistance. 37 Nonetheless, multiple studies reported a discrepancy between the phenotypic resistance and mutation detection.…”
Section: Discussionmentioning
confidence: 99%
“…An unprecedented number of studies last year reported on the important topic of antimicrobial resistance of H pylori strains 24‐60 . These are outlined in Table 1.…”
Section: Antibiotic Resistancementioning
confidence: 99%